STRATEGI PENGURANGAN STIGMA TB MEMBUKA JALAN UNTUK PEMBICARAAN KESEHATAN MENTAL - Wahyuni, Sri; Dewi Setiyawati (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
This study aims to analyze strategies for reducing Tuberculosis (TB) stigma and its impact on mental health discussions in Medan, considering the close relationship between TB stigma and mental health issues. A qualitative method was used, involving in-depth interviews, focus groups, document and media analysis, and participatory observations to gain a deep understanding of perceptions, experiences, and the social context related to TB stigma. The results indicate that public education and information, media engagement, social and psychological support, and public policy and advocacy are key strategies in reducing TB stigma. This not only helps reduce TB-related stigma but also opens up space for improved discussions and support for mental health, showing the importance of a comprehensive approach in addressing TB.